Synthesis of CdS Sensitized TiO2 Photocatalysts: Methylene Blue Adsorption and Enhanced Photocatalytic Activities. (29th February 2016) - Makama, A. B.; Salmiaton, A.; Saion, E. B.; Choong, T. S. Y.; Abdullah, N.
Abstract : A series of CdS/T i O 2 nanocomposites with different Cd to Ti molar ratio were synthesized from P25-T i O 2 nanopowder using microwave-assisted hydrothermal method. The as-produced powders were characterized by XRD, electron microscopy, EDX, and UV-Vis diffuse reflectance spectroscopy. The adsorption capacity and photocatalytic activity of the samples were investigated using methylene blue as a model pollutant. Sorption tests revealed that the adsorption of MB onto the samples obeys the Freundlich-Langmuir isotherm model. The sorption capacity decreased as follows: T i O 2 > T C d 2 > T C d 1 > T C d 3 > T C d 4 . The results of the photocatalytic tests under high-intensity discharge (HID) lamp revealed that CdS/T i O 2 powders with low Cd to Ti molar ratios exhibited much higher activities than P25-T i O 2 . The CdS/T i O 2 sample with 20% CdS/(TCd2) showed the most activity among all these samples. The results also show that the Cd to Ti molar ratio of the nanocomposite has a significant effect on the photodegradation of MB and the enhanced activities exhibited by the nanocomposites are because of the low rate of electron-hole recombination.